Melatonin Increases Fetal Weight in Wild-Type Mice but Not in Mouse Models of Fetal Growth Restriction - Renshall, Lewis J.; Morgan, Hannah L.; Moens, Hymke; Cansfield, David; Finn-Sell, Sarah L.; Tropea, Teresa; Cottrell, Elizabeth C.; Greenwood, Susan; Sibley, Colin P.; Wareing, Mark; Dilworth, Mark R. (Frontiers in Physiology, 2018)
Fetal growth restriction (FGR) presents with an increased risk of stillbirth and childhood and adulthood morbidity. Melatonin, a neurohormone and antioxidant, has been suggested as having therapeutic benefit in FGR. We tested the hypothesis that melatonin would increase fetal growth in two mouse models of FGR which together represent a spectrum of the placental phenotypes in this complication: namely the endothelial nitric oxide synthase knockout mouse (eNOS-/-) which presents with abnormal uteroplacental blood flow, and the placental specific Igf2 knockout mouse (P0+/-) which demonstrates aberrant placental morphology akin to human FGR. Melatonin (5 μg/ml) was administered via drinking water from embryonic day (E)12.5 in C57Bl/6J wild-type (WT), eNOS-/-, and P0+/- mice. Melatonin supplementation significantly increased fetal weight in WT, but not eNOS-/- or P0+/- mice at E18.5. Melatonin did, however, significantly increase abdominal circumference in P0+/- mice. Melatonin had no effect on placental weight in any group. Uterine arteries from eNOS-/- mice demonstrated aberrant function compared with WT but melatonin treatment did not affect uterine artery vascular reactivity in either of these genotypes. Umbilical arteries from melatonin treated P0+/- mice demonstrated increased relaxation in response to the nitric oxide donor SNP compared with control. The increased fetal weight in WT mice and abdominal circumference in P0+/-, together with the lack of any effect in eNOS-/-, suggest that the presence of eNOS is required for the growth promoting effects of melatonin. This study supports further work on the possibility of melatonin as a treatment for FGR.